If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100 + -4x = 41x + 15 Reorder the terms: 100 + -4x = 15 + 41x Solving 100 + -4x = 15 + 41x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-41x' to each side of the equation. 100 + -4x + -41x = 15 + 41x + -41x Combine like terms: -4x + -41x = -45x 100 + -45x = 15 + 41x + -41x Combine like terms: 41x + -41x = 0 100 + -45x = 15 + 0 100 + -45x = 15 Add '-100' to each side of the equation. 100 + -100 + -45x = 15 + -100 Combine like terms: 100 + -100 = 0 0 + -45x = 15 + -100 -45x = 15 + -100 Combine like terms: 15 + -100 = -85 -45x = -85 Divide each side by '-45'. x = 1.888888889 Simplifying x = 1.888888889
| 20=-4t | | 7-9x=62-44x | | 2t+4=16 | | 28u^48-22u^8vy^7= | | 2236000-17740x=2324700 | | 6x^2=6x | | x+1=39 | | 24-(x+3)=12+2(9-2x) | | 4x-5=11-82 | | -x-2y=-3 | | 30=-6t | | 3=-6t | | x^3-3x^2+6x-12=0 | | (2x+4)(4x+6)(6x+8x)=0 | | 2/3a=12-4 | | 49=-x | | x^5=1.25 | | 4x^2+23x+15x=0 | | 3m/2-2/4=9/2-m | | -4b^2+36=0 | | x-7(2x+1)=2(6-5x)-13 | | (6x+7)-(-13x+8)=0 | | 25=x+4 | | (2x+7)(x+1)=28-2 | | -3x-3(z-3)=3 | | x^2-7x-19=-6+1 | | 5-(4x+6)=3x+(7-4x) | | -8=-8+x | | 1/3+2/3m=1/3m-2/3 | | 2(2+3)= | | t=t^2-4t+3 | | M+3+5=21 |